Diverse strategies of teachers in teaching reading comprehension - Tarigan, Fatin Nadifa; Hasibuan, Siti Aminah (UNIB Press, 2024)
This study aims to investigate the strategies used by English teachers to teach reading comprehension and how these strategies are implemented. This study is classified as descriptive qualitative research. The study employed observations, interviews, and documentation as its primary methods. The research's informants were two English teachers. The results showed that the teachers used three different tactics: discussion strategies, question-answer relationships, or QARs, and scaffolding. Scaffolding involves providing support and gradually reducing this support as students become more independent, allowing them to build on their existing knowledge and skills. The QAR strategy, which involves asking questions, answering them, and then reviewing the answers, is particularly effective in deepening understanding and retention of text. Discussion, facilitated by the teacher or in small groups, encourages students to articulate their thoughts and interpretations, fostering a deeper engagement with the material. These strategies, when integrated into reading comprehension instruction, not only support students in developing their reading comprehension skills but also promote a deeper understanding and appreciation of the texts they read.